Geomorphic activity alterations over the implementation of the Port Terminal on the South Coast of Espírito Santo, Brazil - Vervloet, Roberto José Hezer Moreira; Merlo Prata, Pablo (Geografares, 2023)
This paper is the result of a scientific study carried out by the State Institute for the Environment and Water Resources of Espírito Santo. It focuses on the processes of coastal alteration in the Embaiamento Meaípe-Maimbá following the construction of a port terminal in 1977 by the Samarco Mineração company in the community of Ubú, located in the coastal city of Anchieta. The methodology was based on remote sensing techniques, photointerpretation, georeferencing of aerial imagery, beach profile data and calculation of the number of accumulated sediments using the differential equation of the trapezoidal rule. The process of the progradation of the coastline and the determination of the degree of influence of the hydraulic mole of the port terminal on the accumulation of 335,972.68 m³ of sediment in the last 42 years in its southern part and on the erosion in the northern part are also evaluated. This accumulation strongly affects the balance and distribution of sediments along the beaches of the bay, explaining the reduction of the sand strip and the destruction of the edge of Meaípe.